PERAN AKUNTAN DALAM ERA DIGITAL 5.0 DI INDONESIA - Kamaedi (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
ABSTRACT: This study aims to determine the impact of the Industrial Revolution 4.0 from the perspective of the accounting profession, the accounting profession ahead of the Society 5.0 era, and the efforts of accountants to face the digitalization of the economy ahead of the society 5.0 era. This study used a systematic literature review. These sources and research come from books, journals and other literature related to the Role of Accountants in the Digital Era 5.0 in Indonesia. Analysis of research data using VOSviewer – Visualization of scientific landscapes. The results of this study Based on the research that has been done, the accounting profession ahead of Society 5.0 has had many changes when compared to the previous era. Now, accountants can do digital-based records, so it doesn't take much time. Although the opportunity for changing the profession of accountants and auditors with robots is quite large, these roles cannot be completely replaced because there are still several important roles that cannot be performed by robots. Future accountants can also have new professional opportunities, and role expansion. Therefore, to achieve this, accountants need the ability to be able to adapt to technological changes that will continue to develop. These abilities include technology, ways of thinking, and problem solving. Also, the main capabilities that future accountants must have are centered on skills in information technology. Meanwhile, the steps that must be taken by accountants in facing Society 5.0 include awareness, education, career development, and application of high standards.